(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Joint mobilization is a complicated task in terms of learning as well as teaching and is characterized by great inter subject variability. With reference to the acquisition of skills such as joint mobilisation, only a few studies have investigated the effectiveness of the provision of real-time visual feedback on a computer screen in terms of students’ ability to establish optimal force and demonstrate adequate performance. There is lack of training in theory and practical skills in mobilization given to the Physiotherapy students. Thus, an effort has been made in to practice it virtually using Leap Motion Controller. Method: Total 138 participants will be recruited as per the inclusion and exclusion criteria. A brief explanation about the study will be given. Participants will be given exposure to the software and modality being used along with demonstration. Followed by, a questionnaire to evaluate the effective learning using the System Usability Scale. Conclusion: The results from the study will significantly provide efficacy of the simulative device and evidence on the use of LMC for learning joint mobilization using the System Usability Scale.